Patterns of Pronunciation of English Interdental Fricatives by Some Yoruba Speakers of English in a Nigerian University - Fajobi, Eunice O.; Akande, Akinmade T. (Studia Anglica Posnaniensia, 2018)
This paper is an investigation of the pronunciation patterns of English interdental fricatives by some Yoruba speakers of English at Obafemi Awolowo University (OAU), Ile-Ife. This was with a view to finding out the extent to which gender, the level of education, and the position in words of the interdental fricatives (i.e., the (th) variable as in think, pathetic, and path on the one hand, and the (dh) variable as in then, father, and clothe on the other hand) could affect the realisations of these two fricatives, otherwise known as (th) and (dh) variables. Data eventually used for this study were drawn from the reading performance of thirty-three informants who were of Yoruba origin. The thirty-three informants comprised 20 male and 13 female subjects with different levels of education ranging from undergraduate to doctoral. Our findings indicated that the (dh) variable was significantly affected by gender while the (th) variable was not. It was also demonstrated that while the (th) was significantly affected by the level of education of informants, the (dh) variable had no statistically significant association with the speakers’ level of education. Finally, the results of the study revealed that the position in a word (whether initial, medial, or final) of each of the variables affected the realisations of the two variables significantly. It was therefore concluded that sociolinguistic variables such as gender and the level of education were capable of affecting the rendition of linguistic variables significantly.